Greenwashing 2.0 - Lane, Eric L. (Columbia Journal of Environmental Law, 2019)
This Article argues that this period of unprecedented clean tech innovation requires a new paradigm for thinking about greenwashing. Specifically, it is essential that the paradigm shift from almost exclusive focus on B-to-C environmental advertising directed to individual green consumers to an expanded and more nuanced view that also includes B-to-B representations made to commercial consumers. This new paradigm would define greenwashing expansively to include any false or misleading claim regarding the environmental benefit of a product, service, or business practice. Its analysis should not be limited to cases brought by or on behalf of individual consumers, but should also contemplate legal actions by and on behalf of green commercial consumers. Changing the greenwashing paradigm in this way will reflect the commercial realities of the clean tech revolution, and will provide the broader vantage point necessary to identify instances of greenwashing and understand its prevalence and effects.